Documento della Pontificia Commissione Biblica sul popolo ebraico e le sue Sacre Scritture nella Bibbia cristiana - Ghiberti, G. (Liber Annuus, 2001)
Abstract The document of the Pontifical Biblical Commission (PBC), elaborated through an entire five year period, contributes to a discussion which is developing in the Catholic Church from the time of the Second Vatican Council; its continual development is closely followed to this day. A concise synthesis gives direction for the reading of the long and complex text. The overall reception of the document has been favorable; having had a modest start, the discussion does not give signs of halting. The article is interested for the most part in the Hebrew and Christian reading of the Hebrew Bible. The PBC often uses the categories of continuity and discontinuity, seen in the light of coherent development of the OT and the NT. If one is to speak about progress or organic novelty, one must also recognize that both